Emotion Regulation Using Virtual Environments and Real-Time fMRI Neurofeedback - Lorenzetti, Valentina; Melo, Bruno; Basílio, Rodrigo; Suo, Chao; Yücel, Murat; Tierra-Criollo, Carlos J.; Moll, Jorge (Frontiers in Neurology, 2018)
Neurofeedback (NFB) enables the voluntary regulation of brain activity, with promising applications to enhance and recover emotion and cognitive processes, and the underlying neurobiology. It remains unclear whether NFB can be used to aid and sustain complex emotions, with ecological validity implications. We provide a technical proof of concept of a novel real-time functional magnetic resonance imaging (rtfMRI) NFB procedure. With rtfMRI-NFB, we enabled participants to voluntarily enhance their own neural activity while they experienced complex emotions. The rtfMRI-NFB software (FRIEND Engine) was adapted to have a virtual environment as brain computer interface (BCI) and musical excerpts to induce two emotions (tenderness and anguish), aided by participants’ preferred personalized strategies to maximize the intensity of these emotions. Eight participants from two experimental sites performed rtfMRI-NFB on two consecutive days in a counterbalanced design. On one day, rtfMRI-NFB was delivered to participants using a region of interest (ROI) method, while on the other day using a support vector machine (SVM) classifier. Our multimodal VR/NFB approach appeared technically feasible and robust as a method for real-time measurement of the neural correlates of complex emotional states and their voluntary modulation. Via changing the color of the virtual environment BCI during rtfMRI-NFB, participants successfully increased in real time, the activity of the septo-hypothalamic area and the amygdala during the ROI based rtfMRI-NFB, and correctly matched patterns of brain activity to those classified as tenderness and anguish during SVM based rtfMRI-NFB. Offline fMRI analyses confirmed that during tenderness rtfMRI-NFB conditions, participants recruited the septo-hypothalamic area and other regions ascribed to social affiliative emotions (frontal / temporal pole and precuneus). During anguish rtfMRI-NFB conditions, participants recruited the amygdala and other dorsolateral prefrontal and additional regions ascribed to negative affect. These findings were robust appeared at the individual subject level, reflected in self-reported emotion intensity during rtfMRI-NFB and were observed with both ROI and SVM methods and across the two sites. This multimodal VR/rtfMRI-NFB protocol holds promise as an engaging tool for brain-based interventions to enhance adaptive emotional states in normative samples and restore normal states in psychopathologies associated with anxiety, stress or reduced empathy.